KangPiLao decoction modulates cognitive and emotional disorders in rats with central fatigue through the GABA/Glu pathway - Yifei Xu; Yajun Lian; Jie Li; Yifei Zhang; Yan Liu; Xuejiao Wang; Jie Ma; Feng Li (Frontiers in Pharmacology, 2022)
Background: Central fatigue (CF) is a subjective sense of tiredness associated with cognitive and memory disorders, accompanied by reduced physical endurance and negative emotions, such as anxiety and depression. Disease progression and prognosis with regards to CF have been unfavorable and possibly contribute to dementia, schizophrenia, and other diseases. Additionally, effective treatments for CF are lacking. KangPiLao decoction (KPLD) has been widely applied in clinical treatment and is composed of six Chinese herbal medicines, some of which have confirmed anti-fatigue effects. While glutamic acid (Glu) is the main excitatory transmitter in the central nervous system (CNS), gamma-aminobutyric acid (GABA) is the major inhibitory transmitter. Both are involved in emotional, cognitive, and memory functions. This research was designed to explore how KPLD regulates cognitive and emotional disorders in rats with CF and to identify the relationship between the regulatory effect and the GABA/Glu pathway.Methods: The compounds comprising KPLD were analyzed using high-performance liquid chromatography-mass spectrometry. Sixty Wistar rats were randomly divided into six groups. The modified multiple platform method was used to induce CF. Cognitive, emotional, and fatigue states were evaluated by performing behavioral tests (Morris water maze [MWM], open-field test [OFT], and grip strength test). Histomorphology, western blotting, immunohistochemistry, and RT-qPCR were performed to investigate protein and mRNA expression levels in the hippocampus and prefrontal cortexes involved in the GABA/Glu pathway.Results: Rats with CF exhibited impaired spatial cognition and increased negative emotions in the MWM and OFT. KPLD enabled the improvement of these symptoms, especially in the high-concentration group. Western blotting and RT-qPCR demonstrated that the expression of GABAARα1, GABAARγ2, GABABR1, and GAD67 in rats with CF was higher, whereas GAT-1 and NMDAR2B were lower in the hippocampus and prefrontal cortex. KPLD decreased the expression of GABAARα1, GABABR1, GABAARγ2, and GAD67 in the hippocampus and prefrontal cortex and enhanced the expression of NR2B in the prefrontal cortex.Conclusion: KPLD significantly improved cognitive and emotional disorders in rats with CF by regulating the GABA/Glu pathway. Overall, KPLD may be a promising candidate for developing a drug for treating CF.